Leptin : Role over central nervous system in epilepsy (2018)
Adipose tissue is a dynamic organ with different effects on the body. Many of these effects are mediated by leptin, a hormone strongly involved in regulation of feeding and energy metabolism. It has an important role as a mediator of neuronal excitatory activity and higher brain functions. The aim of this study was to review the association between leptin and cerebral neuronal function, in particular its anticonvulsant or convulsant effects and the possible therapeutic role for treating epilepsy. For this purpose, the databases Pubmed, Science Direct, Elsevier, ResearchGate and Scielo were searched to identify experimental studies, reviews and systematic review articles, published in English, Spanish or Portuguese. Experimental studies and the presence of leptin receptors in nervous system sites other than the hypothalamus suggest an influence on higher brain functions. Indeed several animal studies have demonstrated a role of these channels in epileptiform activity as both anticonvulsive and convulsive effects have been found. The reason for these discrepancies is unclear but provides clear evidence of a potential role of leptin and leptin therapy in epileptiform activity. The association between leptin and brain function demonstrates the importance of peripheral metabolic hormones on central nervous system and opens a new way for the development of novel therapeutic interventions in diseases like epilepsy. Nevertheless further investigations are important to clarify the dynamics and diverse actions of leptin on excitatory regulation in the brain. © 2018 The Author(s).